1999
DOI: 10.1002/(sici)1520-6300(1999)11:3<397::aid-ajhb10>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education and marital status on premature mortality among urban adults in Poland, 1988-1989

Abstract: Mortality rates among adults 25–64 years of age (premature mortality) in 1988 and 1989 were compared by educational status (a four‐level scale) and marital status (married vs. nonmarried) in three Polish cities situated in ecologically different regions of Poland. Each of the two social factors has a significant influence on mortality after the effect of the other is controlled statistically. The risk of premature death increases regularly with an individual's decreasing position on the educational scale; also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…As a result of i.a. late marriages and higher rates of mortality among those living alone, the number of single men decreases in a general population during a life-span [14]. For example, in 1988, 74.8% of men aged 20-24 were single, whereas among 45-59-year-old men only 5.8% were never married [15].…”
Section: Methodsmentioning
confidence: 99%
“…As a result of i.a. late marriages and higher rates of mortality among those living alone, the number of single men decreases in a general population during a life-span [14]. For example, in 1988, 74.8% of men aged 20-24 were single, whereas among 45-59-year-old men only 5.8% were never married [15].…”
Section: Methodsmentioning
confidence: 99%
“…In Poland, at the end of the 80s of the last century was performed the study that analyzed the cumulative effect of almost 50 years of socialistic system (before the political transformation) on premature mortality of the Polish urban population. The result of this study showed regular monotonic social gradients within mortality rates: the risk of premature death increased regularly with an individual's decreasing position on the educational scale (Welon et al, 1999). Elo and Preston (1996) pointed out that when studying social differences in mortality in adults, there are certain reasons for preferring the criterion of education over other markers of social position.…”
mentioning
confidence: 68%
“…Married people live longer than their unmarried peers, including those who have never been married, as well as those who are separated, divorced, or widowed. Since the mid 1800s, this has been confirmed in numerous studies from many countries, and is independent of differences in race, geography, politics, or economics (Brajczewski and Rogucka, ; Goldman, ; Hu and Goldman, ; Welon et al, ). On average, mortality rates are lower in married individuals of all ages.…”
Section: Introductionmentioning
confidence: 79%